Hacking the Code : Auditor's Guide to Writing Secure Code for the Web. - Burnett, Mark (Syngress Pub., 2004)
Contains information of dedicated exploit, vulnerability, and tool code along with corresponding instruction. This book also includes a CD which contains both commented and uncommented versions of the source code examples presented throughout, along with a copy of the author-developed Hacker Code Library v1.0.